1987
DOI: 10.1111/j.1095-8339.1987.tb01042.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of pollen morphology in Euphorbiaceae with special reference to Phyllanthus

Abstract: A survey of pollen morphology in Euphorbiaceae with special reference to Phyllanthus. The Euphorbiaceae is a very large family, but the number of publications containing descriptions of pollen grains relatively low. Especially the category of monographic papers is poorly represented. The Webster system is discussed in relation to pollen morphology. It appears that four subfamilies are characterized by a basic pollen type; the subfamily Acalyphoideae is an exception to this generalization. Webster's contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
65
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 31 publications
2
65
0
Order By: Relevance
“…1 G) and Sauropus ( Fig. 10 H), and which results in patterns reminiscent of pantoaperturate Phyllanthus pollen (Punt 1987), might have given rise to such a type in Phyllanthus. At the same time, this suggests some degree of relationship between these genera.…”
Section: Ectoaperture Morphologymentioning
confidence: 98%
See 2 more Smart Citations
“…1 G) and Sauropus ( Fig. 10 H), and which results in patterns reminiscent of pantoaperturate Phyllanthus pollen (Punt 1987), might have given rise to such a type in Phyllanthus. At the same time, this suggests some degree of relationship between these genera.…”
Section: Ectoaperture Morphologymentioning
confidence: 98%
“…The same principle can be applied to Margaritaria cyanosperma and M. scandens, where deviant 2-and 3-syncolporate grains reminiscent of the syncolporate pollen of Phyllanthus (e.g. P. aenaeus-type) (Punt 1967(Punt , 1980(Punt , 1987Bor 1979, Meewis & Punt 1983, Lobreau-Callen et al 1988 were found. However, Pozhidaev (1998Pozhidaev ( , 2000, in his studies of pollen aperture patterns, found similar transformation series in unrelated taxa within the dicotyledons.…”
Section: Ectoaperture Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…The precise usage of pollen characters in taxonomy for the small pollen size, usually around 20 -30 μm diam is difficult, therefore the aid of scanning electronic microscope (SEM) in the observation of the exine ornamentation is necessary. At least 30 pollen types were reported in 220 species of Phyllanthus studied using LM and/or SEM (Erdtman 1952, Webster 1956, 1986, Köhler 1965, Punt 1967, 1980, 1987, Punt & Rentrop 1973, Bor 1979, Meewis & Punt 1983, Long & Yu 1984, Rossignol et al 1987, Lobreau-Callen et al 1988, Chen & Wu 1997, Webster & Carpenter 2002, Wei et al 2002, Sagun & Van der Ham 2003, Santiago et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Pollen morphologically, subfamily Acalyphoideae is the most heterogeneous of the five subfamilies of the Euphorbiaceae (Punt, 1987;Takahashi et al, 1995Takahashi et al, , 2000Nowicke et al, 1998Nowicke et al, , 1999Nowicke & Takahashi, 2002). Pollen of tribe Alchornieae was described by Punt (1962: 7 genera, 14 species, illustrated with drawings), Taka- hashi et al (1995: 5 genera, 15 species, illustrated with SEM and TEM images) and Takahashi et al (2000: 7 genera, 29 species, illustrated with SEM and TEM images).…”
Section: Introductionmentioning
confidence: 99%